2011
DOI: 10.1007/s11295-011-0425-z
|View full text |Cite
|
Sign up to set email alerts
|

Towards genomic selection in apple (Malus × domestica Borkh.) breeding programmes: Prospects, challenges and strategies

Abstract: The apple genome sequence and the availability of high-throughput genotyping technologies have initiated a new era where SNP markers are abundant across the whole genome. Genomic selection (GS) is a statistical approach that utilizes all available genome-wide markers simultaneously to estimate breeding values or total genetic values. For breeding programmes, GS is a promising alternative to the traditional marker-assisted selection for manipulating complex polygenic traits often controlled by many smalleffect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 95 publications
(98 reference statements)
1
67
0
Order By: Relevance
“…Such studies have shown that using these breeding values in association with the phenotype resulted in higher accuracy when selecting new superior genotypes, supporting the approach used in our study (Kumar et al, 2012b;Iwata et al, 2013).…”
Section: Implementing Genomic Selection In Table Grape Breeding Programssupporting
confidence: 81%
“…Such studies have shown that using these breeding values in association with the phenotype resulted in higher accuracy when selecting new superior genotypes, supporting the approach used in our study (Kumar et al, 2012b;Iwata et al, 2013).…”
Section: Implementing Genomic Selection In Table Grape Breeding Programssupporting
confidence: 81%
“…A total of 442 own-rooted seedlings were planted in four rows at 0.5-m Kumar et al, 2012) were used for QTL validation and fine-mapping. The three QTL validation families were grafted on M.9 rootstock and planted in a Plant and Food Research orchard in 2008.…”
Section: Plant Materialsmentioning
confidence: 99%
“…GWS has rarely been applied to fruit trees, being restricted to apples (Kumar et al, 2012), pears (Iwata et al, 2013), and grapes (Viana et al, 2016). To our knowledge, the present study represents the first attempt to investigate the feasibility of genomic selection in Citrus.…”
Section: Introductionmentioning
confidence: 99%